La Corona de Aragón y Escocia: Paralelismos al hilo de Heart of Midlothian - Torquemada Sánchez, María Jesús (Cuadernos de Historia del Derecho, 2007)
The Heart of Midlothian, Sir Walter Scott’s historical novel, offers some keys to undertake a comparative study between the formation and the development of the Hispanic and British nationalisms. Unlike other European countries, the legal traditions and social characteristics of both territories would constitute in serious obstacles and a reason for conflict at the time of forming the new nationalities that were forged in the decline of the Old Regime.